(untitled) (FULafia Journal of Science and Technology, 2023)
fish were exposed to test water separately diluted with acute concentrations of paraquat of 0, 15, 20, 25 and 30mg/L. A 96Hrs exposure to acute concentrations of the toxicant resulted in normocytic-normochromic anaemia in the exposed fish. Blood indices attributable to normocytic-normochromic anaemia was observed with a significant (p<0.05) decrease in haemoglobin, haematocrit, red blood cells compared with fish in the control test: Mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH) and mean corpuscular haemoglobin concentration (MCHC) were not significantly different (p>0.05). White blood cells, lymphocytes, monocytes, Neutrophils, eosinophil and basophil were also not significantly different (p>0.05) with increasing concentrations of the toxicant